How does digitizing the tax system increase taxpayer compliance? / Tutty Nuryati, Uswatun Khasanah and Andika Dwi Hertanto - Nuryati, Tutty; Khasanah, Uswatun; Dwi Hertanto, Andika (UiTM Cawangan Johor, 2023)
Tax revenue, whose percentage reached above 80% of the total revenue of the State Budget in 2021, is the largest component of Indonesia's revenue. However, Indonesia's tax ratio in 2021 was only 9,11 %, according to the Indonesian Ministry of Finance in 2022. Indonesia implements the self-assessment system in collecting taxes, which of course requires the development of a good tax administration information system, such as the implementation of an e-filing information system to perform optimally. E-filing is an electronic-based tax reporting system which enables taxpayers to report via online without having to visit the tax office. This study aims to analyze the effect of the e-filing information system on taxpayers' compliance, directly and through the taxpayers' satisfaction variable on the services they receive. This study utilized path analysis based on Structural Equation Modelling (SEM) as its data analysis technique. The results of the study stated that the successful implementation of the e-filing information system gives a positive effect on taxpayer satisfaction and taxpayers' compliance, meamwhile, taxpayer satisfaction gives a positive effect on taxpayer compliance. Keywords: Tax Revenue, E-filing, Information System Success, Taxpayer Satisfaction, Taxpayer Compliance.